(untitled) (LEARNing Landscapes, 2020)
Performances and artefacts of student learning provide tangible evidence of their understanding of classroom instruction. Hattie (2012, 2015) uses the term visible learning to focus attention on the need for teachers to gather and consider these as evidence of students’ ongoing learning, linking these tightly to teachers’ pedagogical repertoire identified for having impact value. This article describes and illustrates a progression of learning tasks in an Initial Teacher Education (ITE) program that affords insights into students’ beginning ability to complete and execute lesson plans in their first year, first semester of the program.